Aparatur Sipil Negara Non Muslim dalam Penyelenggaraan Ibadah Haji: Manajeman Sumber Daya Manusia berbasis Moderasi Beragama - Rizkyanti, Aulya Nanda; Muhajarah, Kurnia (Sekolah Tinggi Teologi Injili dan Kejuruan (STTIK) Kupang, 2026)
The organization of Hajj is a form of religious public service that involves the management of human resources within Kementerian Agama Republik Indonesia. This study aims to analyze the role of non-Muslim civil servants (ASN) in the organization of the Hajj and the implementation of human resource management based on religious moderation. This research employs a qualitative approach with a case study method through in-depth interviews, observation, and analysis of official Hajj committee documents. Data were analyzed using the Miles and Huberman model through the stages of data reduction, data display, and conclusion drawing. The findings show that three non-Muslim civil servants were involved in the Hajj organization and were assigned to administrative and technical divisions, namely public relations, secretariat, and accommodation. Their placement was based on competence and organizational needs, while ritual-related tasks remained the responsibility of Muslim officers. These findings indicate that the application of the merit system and proportional task distribution reflects the integration of religious moderation in human resource management and supports the effectiveness of Hajj administration.